National and sub-national exposure to ambient fine particulate matter (PM2.5) and its attributable burden of disease in Iran from 1990 to 2016. (December 2019) - Shamsipour, Mansour; Hassanvand, Mohammad Sadegh; Gohari, Kimiya; Yunesian, Masud; Fotouhi, Akbar; Naddafi, Kazem; Sheidaei, Ali; Faridi, Sasan; Akhlaghi, Ali Asghar; Rabiei, Katayoun; Mehdipour, Parinaz; Mahdavi, Mokhtar; et al.
Abstract: Ambient particulate matter is a public health concern. We aimed (1) to estimate national and provincial long-term exposure of Iranians to ambient particulate matter (PM) < 2.5 μm (PM2.5 ) from 1990 to 2016, and (2) to estimate the national and provincial burden of disease attributable to PM2.5 in Iran. We used all available ground measurements of PM < 10 μm (PM10 ) (used to estimate PM2.5 ) from 91 monitoring stations. We estimated the annual mean exposure to PM2.5 for all Iranian population from 1990 to 2016 through a multi-stage modeling process. By applying comparative risk assessment methodology and using life table for years of life lost (YLL), we estimated the mortality and YLL attributable to PM2.5 for five outcomes. The predicted provincial annual mean PM2.5 concentrations range was between 21.7 μg/m 3 (UI: 19.03–24.9) and 35.4 μg/m 3 (UI: 31.4–39.4) from 1990 to 2016. We estimated in 2016, about 41, 000 deaths (95% uncertainty interval [UI] 35634, 47014) and about 3, 000, 000 YLL (95% UI: 2632101, 3389342) attributable to the long-term exposure to PM2.5 in Iran. Ischemic heart disease was the leading cause of mortality by 31, 363 deaths (95% UI: 27520, 35258), followed by stroke (7012 (5999, 8062) deaths), lower respiratory infection (1210 (912, 1519) deaths), chronic obstructive pulmonary disease (1019 (715, 1328) deaths), and lung cancer (668 (489, 848) deaths). In 2016, about 43% of all PM2.5 related mortality in Iran was, respectively, in the following provinces: Tehran (12.6%), Isfahan (9.3%), Khorasan Razavi (8.0%), Fars (6.5%), and Khozestan (6.4%). In summary, we found that the majority of Iranians were exposed to the levels of ambient particulate matter exceeding the WHO guidelines from 1990 to 2016. Further, we found that there was an increasing trend of total mortality attributed to PM2.5 in Iran from 1990 to 2016 where the slope was higher in western provinces. Graphical abstract: Image 1 Highlights: Estimated national and subnational long-term exposure to ambient PM2.5 in Iran for 27-year period. Estimated Burden of Disease attributable to ambient PM2.5 in Iran for 27-year period. Only in 2016, about 41, 000 deaths could be attributable to ambient PM2.5 in Iran. The slope of total mortality increase attributable to ambient PM2.5 was higher in western provinces. The COPD death rate attributable to PM2.5 had the largest increase from 1990 to 2016 in Iran.